2014
DOI: 10.7869/tg.187
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL28B single nucleotide polymorphism rs8099917 with response to treatment in genotype 3 HCV-infected patients from India

Abstract: Background and aim:IL28B gene polymorphisms have been associated with treatment-response (sustained virological response, SVR) in genotype 1 hepatitis C virus (HCV)-infected patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Similar result for minor allele frequency was also reported for Indian populations in a study conducted earlier using one SNP only in a healthy control group (0.238 for rs12979860 T allele) from southern region of India, the state of Andhra Pradesh [27] and pooled samples CHC cases (0.17 for rs8099917 G allele) [7]. We have derived haplotypes from both SNPs in healthy control and CHC cases by LD plot to determine population divergence to assess whether alleles at flanking loci on the same chromosomes tend to be inherited together or are there any associated ancestral recombination events.…”
Section: Discussionsupporting
confidence: 87%
“…Similar result for minor allele frequency was also reported for Indian populations in a study conducted earlier using one SNP only in a healthy control group (0.238 for rs12979860 T allele) from southern region of India, the state of Andhra Pradesh [27] and pooled samples CHC cases (0.17 for rs8099917 G allele) [7]. We have derived haplotypes from both SNPs in healthy control and CHC cases by LD plot to determine population divergence to assess whether alleles at flanking loci on the same chromosomes tend to be inherited together or are there any associated ancestral recombination events.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore there are certain genetic variations especially the one near the IL-28B gene have been associated with response to HCV therapy with peg-Interferon and ribavirin. Though these IL-28B gene polymorphisms may have a lesser role to play in the era of DAAs certain studies [22,23] have shown that such gene polymorphisms are associated with virolological response rates in both genotype 1 and genotype 3.…”
Section: Genotypementioning
confidence: 99%
“…[ 4 8 10 11 12 13 27 ] Such studies are of paramount importance for better diagnosis, prognosis and management of disease. [ 28 29 30 ]…”
Section: Discussionmentioning
confidence: 99%